2018
DOI: 10.1111/fwb.13072
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter traits drive community structure and functioning in a natural aquatic microcosm

Abstract: Leaf litter fuels secondary production in many aquatic ecosystems. Although the identity and species richness of leaf litter have been shown to influence ecosystem functioning and food‐web composition, it has been challenging to relate such patterns to mechanisms based on litter traits. Here, we investigate how six different leaf litter species, and their mixture, affect litter decomposition, as well as the colonisation and survival of associated aquatic invertebrates in natural microecosystems (tank bromeliad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 64 publications
(115 reference statements)
1
15
0
Order By: Relevance
“…Although such findings have emerged from studies in streams, they are not limited to these ecosystems. Previous studies using tank bromeliads reported similar patterns in litter decomposition 41,48,60 . Indeed, in our study we did not detect differences in decomposition between the two mesh sizes after 80 days, which reinforces the role of microorganisms as the main decomposers in tank bromeliads.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Although such findings have emerged from studies in streams, they are not limited to these ecosystems. Previous studies using tank bromeliads reported similar patterns in litter decomposition 41,48,60 . Indeed, in our study we did not detect differences in decomposition between the two mesh sizes after 80 days, which reinforces the role of microorganisms as the main decomposers in tank bromeliads.…”
Section: Discussionmentioning
confidence: 60%
“…They suggest that these organisms may be resistant or resilient to changes in temperature as they live in small water bodies and are frequently exposed to temperature variation, being adapted to these environment 4 . However, we cannot rule out the possibility that our coarse-mesh bags may have prevented access to litter for some invertebrate detritivores and thus decreased their effect on overall decomposition, despite previous studies in tank bromeliads also did not find effects of invertebrate detritivores on decomposition 41,48,59 . On the other hand, recent studies have shown that although microorganisms may be the major decomposers of organic matter in bromeliads, macroinvertebrates may have an important role in the interactions with microorganisms 41 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…b, Migliorini et al. ). Although taking a trait‐based approach to understanding the effects of litter in lentic systems remains in its infancy, it promises a pathway toward generalizing the role of litter quality and ultimately providing a tangible link between concepts of subsidy quantity and quality.…”
Section: Theme 2: Leaf Litter Quantity Vs Qualitymentioning
confidence: 97%
“…Previous studies have reported declines in species abundances with increasing litter C:N ratios (Richardson, Richardson, Scatena, & Mcdowell, 2000). Also, changes in the litter N:P ratios can influence the survivorship (Migliorini, Srivastava, & Romero, 2018) and performance of aquatic insects living in tank bromeliads (González, Romero, & Srivastava, 2014). Tank bromeliads have been successfully used as natural microcosms to investigate the isolated impacts of environmental changes, such as rainfall regimes, warming and productivity, on community structure and ecosystem functioning (Amundrud & Srivastava, 2016;Antiqueira, Petchey, & Romero, 2018;Bernabé et al, 2018;Dézerald, Céréghino, Corbara, Dejean, & Leroy, 2015;Pires et al, 2016).…”
Section: Introductionmentioning
confidence: 99%